Religious affiliation as a driver of immunization coverage: Analyses of zero-dose vaccine prevalence in 66 low- and middle-income countries - Santos, Thiago M.; Cata-Preta, Bianca O.; Wendt, Andrea; Arroyave, Luisa; Hogan, Daniel R.; Mengistu, Tewodaj; Barros, Aluisio J. D.; Victora, Cesar G. (Frontiers in Public Health, 2022)
Background The literature on the association between religion and immunization coverage is scant, mostly consisting of single-country studies. Analyses in low and middle-income countries (LMICs) to assess whether the proportions of zero-dose children vary according to religion remains necessary to better understand non-socioeconomic immunization barriers and to inform interventions that target zero-dose children. Methods We included 66 LMICs with standardized national surveys carried out since 2010, with information on religion and vaccination. The proportion of children who failed to receive any doses of a diphtheria-pertussis-tetanus (DPT) containing vaccine – a proxy for no access to routine vaccination or “zero-dose” status – was the outcome. Differences among religious groups were assessed using a test for heterogeneity. Additional analyses were performed controlling for the fixed effect of country, household wealth, maternal education, and urban-rural residence to assess associations between religion and immunization. Findings In 27 countries there was significant heterogeneity in no-DPT prevalence according to religion. Pooled analyses adjusted for wealth, maternal education, and area of residence showed that Muslim children had 76% higher no-DPT prevalence than Christian children. Children from the majority religion in each country tended to have lower no-DPT prevalence than the rest of the population except in Muslim-majority countries. Interpretation Analyses of gaps in coverage according to religion are relevant to renewing efforts to reach groups that are being left behind, with an important role in the reduction of zero-dose children.